Shiga Toxin-Bearing Microvesicles Exert a Cytotoxic Effect on Recipient Cells Only When the Cells Express the Toxin Receptor - Johansson, Karl; Willysson, Annie; Kristoffersson, Ann-Charlotte; Tontanahal, Ashmita; Gillet, Daniel; Ståhl, Anne-lie; Karpman, Diana (Frontiers in Cellular and Infection Microbiology, 2020)
Abstract Shiga toxin is the main virulence factor of non-invasive enterohemorrhagic Escherichia coli strains capable of causing hemolytic uremic syndrome. Our group has previously shown that the toxin can reach the kidney within microvesicles where it is taken up by renal cells and the vesicles release their cargo intracellularly, leading to toxin-mediated inhibition of protein synthesis and cell death. The aim of this study was to examine if recipient cells must express the globotriaosylceramide (Gb3) toxin receptor for this to occur, or if Gb3-negative cells are also susceptible after uptake of Gb3-positive and toxin-positive microvesicles. To this end we generated Gb3-positive A4GALT–transfected CHO cells, and a vector control lacking Gb3 (CHO-vector cells), and decreased Gb3 synthesis in native HeLa cells by exposing them to the glycosylceramide synthase inhibitor PPMP. We used these cells, and human intestinal DLD-1 cells lacking Gb3, and exposed them to Shiga toxin 2-bearing Gb3-positive microvesicles derived from human blood cells. Results showed that only recipient cells that possessed endogenous Gb3 (CHO-Gb3 transfected and native HeLa cells) exhibited cellular injury, reduced cell metabolism and protein synthesis, after uptake of toxin-positive microvesicles. In Gb3-positive cells the toxin introduced via vesicles followed the retrograde pathway and was inhibited by the retrograde transport blocker Retro-2.1. CHO-vector cells, HeLa cells treated with PPMP and DLD-1 cells remained unaffected by toxin-positive microvesicles. We conclude that Shiga toxin-containing microvesicles can be taken up by Gb3-negative cells but the recipient cell must express endogenous Gb3 for the cell to be susceptible to the toxin.